2002
DOI: 10.1080/10402000208982584
|View full text |Cite
|
Sign up to set email alerts
|

EHL Film Thickness Limitation Theory Under a Limiting Shear Stress

Abstract: It is nrmterically shown that tlte elastohydrodynamic lubricashon~s that, in elastol~ydrodynan~ic line contacts, the central film tion (EHL) filnt tltickness ltas a linlit ut~der an assumed limiting tliickness is of ntolecular scale and part of the cottract area is in shear stress of the cotttact-lubricant interface in isotlzermal pure non-continuum film lubricatior~ when the equivalent cylinder crrrrolling line contacts. Tlte prediction of the central film thickness vature radirrs is less than the critical on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…where p is the fluid pressure, p s is the fluid solidification pressure, t l0 is the bulk fluid shear strength at ambient pressure, and a tl is the bulk fluid shear strength-pressure proportionality. The correctness and accuracy of equation (2) for predicting the shear strength of the usual fluid at both low and high pressures were confirmed by both the experimental results of Hoglund and Jacobson (1986) and the researches of EHL by Zhang et al (2001aZhang et al ( , 2002bZhang et al ( , 2004a. Equation (2) usually predicts much lower shear strengths of the fluid at low pressures than equation (1).…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…where p is the fluid pressure, p s is the fluid solidification pressure, t l0 is the bulk fluid shear strength at ambient pressure, and a tl is the bulk fluid shear strength-pressure proportionality. The correctness and accuracy of equation (2) for predicting the shear strength of the usual fluid at both low and high pressures were confirmed by both the experimental results of Hoglund and Jacobson (1986) and the researches of EHL by Zhang et al (2001aZhang et al ( , 2002bZhang et al ( , 2004a. Equation (2) usually predicts much lower shear strengths of the fluid at low pressures than equation (1).…”
Section: Introductionmentioning
confidence: 59%
“…The analytical EHL results based on equation (2) as obtained by Zhang et al (2001aZhang et al ( , b, 2002bZhang et al ( , 2004a are qualitatively different from those based on equation (1) as obtained by Jacobson and Hamrock (1984) and Shieh and Hamrock (1991). Actually, the analytical EHL results based on equation (2) incorporating the fluid shear strength and contact-fluid interfacial slippage effects are very fresh and seem of a milestone in the research of EHL as can be found from the researches of EHL by Zhang et al (2001bZhang et al ( , 2002bZhang et al ( , 2004a. Zhang (2003aZhang ( , 2004aZhang ( , 2002a proposed that precisely to say, in isothermal EHL, the material shear strength of effects is actually the contact-fluid interfacial shear strength instead of the fluid shear strength due to the maximum value of the fluid film shear stress across the film thickness occurring at the contact-fluid interface instead of within the fluid film in this EHL and thus the fluid film slippage occurring at the contact-fluid interface caused by the fluid film shear stress at the contact-fluid interface exceeding the contact-fluid interfacial shear strength.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations